Multi-sensory evaluation of urban design in creating obesity encouraging environments: The experience of town centres in Auckland, New Zealand - Parekh, Jayesh; Liu, Wen; Beattie, Lee (Frontiers in Sustainable Cities, 2023)
This article presents a multi-sensory study on pedestrian activities in the public realm of two town centres in Auckland, New Zealand. We utilise mixed-method and multi-sensory evaluation methods, combined with sensory experience and activity mapping, to explore the effects of the obesogenic qualities of town centres on the activity concentrations of pedestrians. We further discuss the influences of urban design and land use diversity on generating obesogenic environments of town centres. The article aims to provide a basis to initiate discussion around the importance of understanding the multiple-sensory experience of public space beyond merely sight sense which traditionally dominates urban design discipline. Furthermore, this article demonstrates the role and quality of sensory experience in shaping obesogenic behaviours encouraging built environment in two town centres with different land use diversity and quality of uses. It also highlights that the mere provision of urban morphology or built form factors linked with walking activities is not a precursor for healthier communities. Thus, the impacts of urban design and quality uses of the built environment on the multiple senses of the users should be considered in urban design research and practices.